The interpretation of the Constitution between legal positivism of modernity and “state of security” (Società e diritti, 2016)
Legal positivism of modernity, built on the will of the legislature, today is interesting, considering its differences with the logical legal positivism, because it is based on a political decision. Because of its construction on willed decision, is intertwined with the need a constant recourse to the courts of justice to settle questions pre or post legal, reguarding radical anthropological or existential problems of one man or of the whole policy society. The Swedish example can be used as an important model for understanding where a possible corrective methodology legal-hermeneutics of the high courts of justice is going. It also helps to better understand the recent security legislations, in some countries - including European countries - against terrorism, without any opposition of national and supranational political and legal systems. Key words: Legal-positivism of modernity, Legal-hermeneutics, Security state.